Adherence to treatment of children and adolescents recently diagnosed with auto-immune Rheumatic Diseases during the COVID-19 pandemic - Ilana Izidoro da Silva; Vanessa Bugni Miotto e Silva; Fernanda Souza Angotti Carrara; Daniela Gerent Petry Piotto; Claudio Arnaldo Len; Maria Teresa Terreri (Elsevier, 2023)
Objectives: Adherence problems have a great impact on auto-immune Rheumatic Diseases (AIRD). The COVID-19 pandemic may have worsened treatment adherence. The aims of this study were to measure treatment adherence to identify an earlier risk of poor adherence and measure families' satisfaction with the health service during the pandemic. Methods: Prospective observational study with 50 parents/children and adolescents with recent AIRD diagnosis. Initially, they answered questions (demographic data, disease) and completed the Pediatric Rheumatology Adherence Questionnaire (PRAQ), after 6 months they completed the Morisky-Green Test (MGT), Brief Medication Questionnaire (BMQ), Compliance Questionnaire for Rheumatology (CQR-19) and Pediatric Quality of Life Inventory Questionnaire 3.0 (PedsQlTM-SSS). The patient's medical records from the previous 12 weeks were reviewed for global and medication adherence data. Results: The mean global adherence score was 94.3 ± 10.0, for medication adherence 97.3 ± 9.3, and for PRAQ questionnaire 5.2 ± 1.5. The authors observed agreement between MGT, BMQ, CQR-19, PedsQLTM-SSS scores and medication adherence rate, but not with global adherence rate. There were no associations between demographic characteristics, disease diagnosis, and adherence. No associations between PRAQ scores and values and global/medication adherence rates were observed. No variables were shown to be predictors of good adherence. The mean PedsQLTM-SSS rate was 92.1 ± 6.8. Conclusion: The high values of MGT, BMQ, CQR-19 questionnaire scores were in agreement with the medication adherence rate. Despite the pandemic, the global and medication adherence rates were good. It was not possible to demonstrate the PRAQ's predictive power. The authors weren't able to establish an association between families' satisfaction and treatment adherence rates.